(untitled) (Revista Brasileira Multidisciplinar, 2019)
Mentha piperita L. has been studied by our group as a possible phytopharmacological drug for treatment of diseases that promote intense inflammatory responses mediated by eosinophils and neutrophils. Thus, the analysis of antioxidant effects and cytokine production by these cells is important to understand the effect of these compounds on the innate and effector phase of adaptive immune response. In this way, an essential oil from M. piperita (Mentaliv®) was used and the myeloperodase enzyme activity (MPO) in neutrophils was evaluated by luminol-dependent chemiluminescence assay (QLDLum) and lucigenin (QLDLuc). The levels of IL-4, IL-6 and TNF-α and QLDLum in eosinophils were also evaluated. Our results showed an inhibition of the production of superoxide anionic radicals and NADPH oxidase in neutrophils after the essential M. piperita oil treatment. However, IL-4 levels were increased after treatment. These data suggest that this phytopharmaceutical has anti-inflammatory activity, by controlling the secreted products during the inflammatory responses, mainly as can occur during infections and chronic inflammatory processes of several diseases, which present a strong tissue eosinophilia with significant presence of PMN in blood and tissue.